Tactical skills of world-class youth soccer teams - Kannekens, R.; Elferink-Gemser, M. T.; Visscher, C. (Journal of Sports Sciences, 2009)
In this study, we examined the relationship between tactical skills and competitive standard of two youth soccer teams by comparing 18 players (age 18-20 years) from the Dutch and 19 players (age 18-23 years) from the Indonesian national youth team. All players completed the declarative and procedural knowledge scales of the Tactical Skills Inventory for Sport (TACSIS). Multivariate analyses of variances and effect sizes were conducted to assess between- and within-team differences. There was a positive relationship between competitive standard and level of tactical skills: the higher-ranked (FIFA World Ranking 2005-2006; http://www.fifa.com) Dutch players outscored their Indonesian counterparts on the TACSIS subscales "knowing about ball actions" (F1,36 = 10.58, P < 0.01), "knowing about others" (F1,36 = 28.88, P < 0.01), and "positioning and deciding" (F1,36 = 10.10, P < 0.01). Multivariate analysis of variance revealed no relationship between tactical skills and playing time (P > 0.05) in the Dutch team, whereas in the Indonesian team one procedural knowledge factor ("positioning and deciding") did show a positive association (effect size = 0.99). In conclusion, tactical skills are fundamental to high-level soccer performance. Ample, expert-led training and match experience at a high competitive standard, starting at a young age, and high-quality talent development programmes are suggested as key ingredients for the development of good tactical skills.